PROSEDUR ATAS PERJALANAN DINAS PADA AUDITORAT KEUANGAN NEGARA I BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA - Ayu Wandira Sania Putri (2021)
This writing aims to find out in more detail the procedures for official travel from administration to accountability reporting as well as to find out what costs and documents are used in official travel procedures at the State I Financial Auditorate of the Supreme Audit Agency of the Republic of Indonesia. The background of this writing is because official travel is an important thing for the Supreme Audit Agency, because it is closely related to the implementation of its main tasks. In this paper, it is intended to obtain an in-depth description of the Official Travel Procedure at the State Financial Auditorate I of the Supreme Audit Agency of the Republic of Indonesia. In the official travel procedure, it is described how the process of issuing a letter of assignment, the process of submitting and disbursing initial invoices, and reporting accountability for the implementation of official travel. Based on the discussion on official travel procedures at the State I Financial Auditorate, it has been running very well and is effective and efficient because it also uses technological aids in the form of applications and is in accordance with applicable laws and regulations.